Feasibility of space solar power for remote mining operations. (September 2021) - Proctor, Nicholas; Shojaeddini, Ensieh; Abbud-Madrid, Angel; Maniloff, Peter; Lange, Ian
Abstract: The market for space solar power (SSP) is developing. This analysis utilizes a case study of SSP for remote mine operations to determine its economic feasibility. We employ a discounted cash flow (DCF) evaluation and then assess the sensitivity of the DCF model to changes in its underlying assumptions. The results indicate that there are scenarios for SSP where it is considered a viable power alternative. Further, a discussion of the assumed manufacturing and transportation costs decreases to expand the market is given. Highlights: A business model of a space solar power system is analyzed for a remote mining operation. Remote mining operations are ideal niche markets for space solar power given the alternative price of electricity they face. Results show some scenarios where space solar power is cost competitive for remote mining operations. Niche markets, like remote mining operations, can help space solar power gain a larger footing in the electricity market.